Experience of Community Leaders in Taking off Pasung (Physical Restraint) for People with Mental Disorders in Southeast Sulawesi - Abdul Patawari; Titin Andri Wihastuti; Nurul Muslihah (International Journal of Science and Society, 2020)
Mental health problems in Indonesia are still severe, WHO SEARO data for 2017 said that Indonesia is ranked second after India, which is 9. 162. Eight hundred eighty-six patients or around 3.7% of the population. Mismanagement of health where there are still many people with mental disorders who experience mounting actions that require attention and involvement of all parties, including community leaders. The purpose of writing this research is to explore the experience of community leaders in carrying out pasung (physical restraint) on people with mental disorders in Southeast Sulawesi. The method that researchers use is qualitative research with a phenomenological interpretative. Participants, as many as 7 (seven) people and selected with a purposive sampling approach, were then analyzed using Interpretative Phenomenological Analysis (IPA). The results of the study found three themes, namely community and family stigma against ODGJ (people with a mental disorder), reasons for retention actions and challenges of community leaders in the release of pasung. The conclusion is that the process of releasing pasung cannot be separated from the experience of a figure in the community so that by involving them is expected to eliminate the act of retention in the community.